Fibriblas dalam penyembuhan luka Pengaruh Nanoemulgel Jintan Hitam (Nigella sativa) Terhadap Jumlah Fibroblas Dalam Penyembuhan Luka Pasca Pencabutan Gigi - Nagita Dari Karini; Rizki Amalina; Yunita Styaningrum (Denta Journal Kedokteran Gigi, 2024)
Background: Tooth extraction is said to be successful when accompanied by a good wound healing process. Innovation for post-tooth extraction wound treatment is necessary. Black cumin has active ingredients that function as anti-inflammatories. The formulation used is nanoemulgel because it has the advantages of stability and good adhesion. Objective: To evaluate the effect of black cumin nanoemulgel on the number of fibroblasts in the wound healing process after tooth extraction in rats. Methods: This study was conducted using post-test only control group design with a total sample of 22 samples divided into 4 groups with each group totaling 5 samples and 2 samples as a drop out. The application is carried out as much as 3 times a day for 5 days. Tissue collection from experimental animals was carried out and then histology preparations were made. Calculations of fibroblast were carried out using hematoxylin eosin (HE) staining and carried out in the apical 1/3 of the 3 visual fields with a V pattern. Statistical tests used are the One-Way Anova test and the Post Hoc LSD test. Results: There was significant difference in the number of fibroblasts between groups (p = 0.000). Black cumin nanoemulgel concentration of 15% showed highest number of fibroblasts. Conclusion: Nanoemulgel black cumin (Nigella sativa) 15% can increase the number of fibroblasts in wound healing post tooth extraction in rats. Nanoemulgel black cumin (Nigella sativa) 15% have the potential to accelerate wound healing process by increasing the number of fibroblasts.